Evaluation of portal vein variations in multidetector CT - Ulusoy, Mahinur; Bolatlı, Güneş; Koplay, Mustafa; Acar, Musa; Zararsız, İsmail (Journal of Surgery and Medicine, 2020)
Aim: It is important for surgeons to have a comprehensive knowledge of vascular anatomy when performing liver interventions. For example, liver transplantation requires a vast understanding of vascular anatomy and variations. This study aimed to evaluate the intrahepatic branching pattern of the portal vein to find out unknown variations. Methods: Multidetector computed tomography images of the abdomen region were used from the PACS archives of Selcuk University Medical Faculty Hospital. Images of 838 patients (464 females and 374 males) who had no hepatic pathologies were examined. Images were evaluated in terms of the presence of variations, and the cases were divided into groups, all of which were compared in terms of gender. Results: A previously unknown variation of the portal vein was detected in 4.9% of the patients: The left portal vein curved reversely after its origination from the main portal vein, supplying liver segments II and IV, after which it branched to supply segment III. In addition, four types of previously known variations of the portal vein were detected. Normal anatomic branching of portal vein was detected in 82.6% of the patients. Conclusion: A previously unknown variation was detected. Awareness of this variation and other known variations is significant in hepatic transplantation, surgery, and interventions.